2008
DOI: 10.1073/pnas.0802776105
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the aldo-keto reductase pathway of polycyclic aromatic trans -dihydrodiol activation in human lung A549 cells

Abstract: 8-oxo-dGuo ͉ DNA strand breaks ͉ tobacco carcinogens ͉ reactive oxygen species P olycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants, which are produced as a result of fossil-fuel combustion and are found in car exhaust and charbroiled and smoked foods (1, 2). They are also present as mixtures in tobacco smoke and are implicated in the causation of human lung cancer (3). To exert their carcinogenic effects, PAHs must be metabolically activated to DNA-damaging agents that will result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
106
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 40 publications
6
106
2
Order By: Relevance
“…This metabolic activation led to the formation of ROS and 8-oxo-dGuo lesions in cellular DNA. Importantly, the amount of ROS and 8-oxo-dGuo formed in these experiments was increased in the presence of a COMT inhibitor (22). This suggested that COMT could intercept the catechol and prevent redox cycling.…”
mentioning
confidence: 65%
“…This metabolic activation led to the formation of ROS and 8-oxo-dGuo lesions in cellular DNA. Importantly, the amount of ROS and 8-oxo-dGuo formed in these experiments was increased in the presence of a COMT inhibitor (22). This suggested that COMT could intercept the catechol and prevent redox cycling.…”
mentioning
confidence: 65%
“…PAH o-quinones also cause oxidative DNA damage in vitro and in vivo (22)(23)(24)(25). Nanomolar concentrations of PAH o-quinones under redox cycling conditions (NADPH and Cu(II)) lead to significant 8-oxo-dGuo formation in bulk DNA, and the responsible oxidant was found to be singlet oxygen ( 1 O 2 ) (24,26).…”
mentioning
confidence: 99%
“…Recently, using either a hOGG1-coupled comet assay or an immunoaffinity capture-stable isotope dilution liquid chromatography/electrospray ionization/multiple reaction monitoring/mass spectrometry (LC/ESI/MRM/MS) assay, it was shown that both the AKR substrate (B[a]P-7,8-trans-dihydrodiol) and the AKR product (B[a]P-7,8-dione) caused significant DNA strand breaks and 8-oxo-dGuo formation in human lung adenocarcinoma A549 cells (25 PAH o-quinones are ligands for the aryl hydrocarbon receptor (AhR) (30). These quinones can promote translocation of AhR to nucleus to induce P4501A1 expression.…”
mentioning
confidence: 99%
“…An investigation of metabolic activation of BP in human lung A549 cells has provided evidence that the AKR-mediated pathway to generate the BP quinone and ROS is operative in these cells. 16 And human bronchoalveolar H358 cells were recently introduced as a model for study of PAH metabolism in normal human lung cells. 17,18 In this connection, development of a stable isotope dilution liquid chromatography tandem mass spectrometric method for analysis of the metabolites of BP and its nucleoside adducts was also described.…”
Section: Introductionmentioning
confidence: 99%